Halophytes Differ in Their Adaptation to Soil Environment in the Yellow River Delta: Effects of Water Source, Soil Depth, and Nutrient Stoichiometry - Li, Tian; Sun, Jingkuan; Fu, Zhanyong (Frontiers in Plant Science, 2021)
The Yellow River Delta is water, salt and nutrient limited and hence growth of plants depend on the surrounding factors. Understanding the water, salt and stoichiometry of plants and soil systems from the perspective of different halophytes is useful for exploring their survival strategies. Thus, a comprehensive investigation of water, salt and stoichiometry characteristics in different halophytes and soil systems was carried out in this area. Results showed that oxygen isotope (δ18O) of three halophytes were significantly different (P < 0.05). Phragmites communis primarily used rainwater and soil water, while Suaeda salsa and Limonium bicolor mainly used soil water. The contributions of rainwater to three halophytes (P. communis, S. salsa, and L. bicolor) were 50.9%, 9.1% and 18.5%, respectively. The carbon isotope (δ13C) analysis showed that P. communis had the highest water use efficiency, followed by S. salsa and L. bicolor. Na+ content in the aboveground and underground parts of different halophytes was all followed an order of S. salsa > L. bicolor > P. communis. C content and N:P in leaves of P. communis and N content of leaves in L. bicolor were significantly positively correlated with Na+. Redundancy analysis (RDA) between plants and each soil layer showed that there were different correlation patterns in the three halophytes. P. communis primarily used rainwater and soil water with low salt content in 60-80 cm, while the significant correlation indexes of C:N:P stoichiometry between plant and soil were mainly in 20-40 cm soil layer. In S. salsa, the soil layer with the highest contribution of soil water and the closest correlation with the C:N:P stoichiometry of leaves were both in 10-20 cm, while L. bicolor were mainly in 40-80 cm soil layers. So the sources of soil water and nutrient of P. communis were located in different soil layers, while there were spatial consistencies of soils in water and nutrient utilization of S. salsa and L. bicolor. These results are beneficial to a comprehensive understanding of the adaptability of halophytes in the Yellow River Delta.